2020
DOI: 10.1093/intqhc/mzaa158
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 is having a destructive impact on health-care workers’ mental well-being

Abstract: Background The coronavirus disease 2019 (COVID-19) may aggravate workplace conditions that impact health-care workers’ mental health. However, it can also place other stresses on workers outside of their work. This study determines the effect of COVID-19 on symptoms of negative and positive mental health and the workforce’s experience with various sources of support. Effect modification by demographic variables was also studied. Methods A cross-sectional survey study, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
183
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 33 publications
14
183
1
5
Order By: Relevance
“…This approach has been developed in several countries in addition to Spain [18,19]. This is particularly relevant because some current data in Spain using the EASE scale are suggesting that during the third wave, the level of distress reported by health care professionals is increasing up to 3 times, with 8.8% of respondents being classified into the fourth category of scores, probably as a result of accumulated fatigue and a feeling of starting over [5]. Therefore, caring for those who care has become a priority for public health strategies [20,21].…”
Section: Principal Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…This approach has been developed in several countries in addition to Spain [18,19]. This is particularly relevant because some current data in Spain using the EASE scale are suggesting that during the third wave, the level of distress reported by health care professionals is increasing up to 3 times, with 8.8% of respondents being classified into the fourth category of scores, probably as a result of accumulated fatigue and a feeling of starting over [5]. Therefore, caring for those who care has become a priority for public health strategies [20,21].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Stress, hypervigilance, fatigue, difficulty sleeping, inability to relax, and fear were common symptoms among health care professionals at the start of the pandemic [5]. The content validity analysis conducted in this study identified behaviors and responses related to these symptoms; the EASE scale items seek to assess the scale's effect on those who provide care to COVID-19 patients.…”
Section: Principal Findingsmentioning
confidence: 99%
See 3 more Smart Citations